Evaluation of protein tyrosine phosphatase activity in patients with acute leukemia - Akdogan, Elif; Cengiz, Sevil; Yılmaz, Mustafa; Sönmez, Mehmet; Durmus, Ahmet; Oval, Ercüment; Omay, Serdar Bedii (Contemporary Oncology/Współczesna Onkologia, 2013)
Protein tyrosine phosphatases regulate physiological processes including growth, differentiation, metabolism and the cell cycle. Together with tyrosine kinases, they control the phosphorylation state of tyrosine residues of signaling proteins. An increased level of protein phosphorylation results in abnormal proliferation and many cancer types show a mutation or deletion of a protein tyrosine phosphatase gene. In this study we evaluated the protein tyrosine phosphatase activity in acute leukemia patients. Tyrosine phosphatase activity in bone marrow mononuclear cells of acute leukemia patients was measured using a tyrosine phosphatase assay system kit and compared with a control group. We found that tyrosine phosphatase activity in acute leukemia patients was high compared to the controls. According to subgroups of acute leukemia, tyrosine phosphatase activity in the AML-M2 subgroup was high compared to the controls. The effect of increased level of protein tyrosine phosphatase activity on leukemogenesis needs further evaluation. Studies in a large group of patients are needed to emphasize the importance of tyrosine phosphatase activity in acute leukemia patients.